Influence of Firm Characteristics on the Impact of Disclosure and Transparency in the Performance of Companies Listed in Nairobi Securities Exchange - Prof. Hazel Gachunga, Edward Kandiru Maina; , Prof. Martin Ogutu, , Prof. Willy Muturi (International Journal of Scientific Research and Management (IJSRM), 2017)
The performance of companies listed in the Nairobi Securities Exchange (NSE) has come under intensescrutiny after a general decline in market share prices of a number of firms between the years 2011–2015due to poor corporate governance practices. This study examined the relationship between disclosure &transparency and performance of listed companies at NSE with firm’s characteristics as the moderatingvariable. The study was anchored on Agency theory and Signaling theory. The study adopted bothdescriptive and correlational research designs on all 60 companies listed in Nairobi Securities Exchangeduring the period 2011-2015. Primary data was collected from companies CEOs or their representativeswhereas secondary data was obtained from the Capital Markets Authority and NSE. Descriptive statistics(mean and standard deviation) and inferential statistics (Pearson correlation and multiple regression) wereused to analyze the data. Findings showed a significant relationship between disclosure & transparencyand performance of firms listed at the NSE and that firm’s characteristics had a moderating effect on therelationship between disclosure and transparency and firm performance. Moderation was supported, sincethe calculated p value of the interaction was 0.000